Sistema socioeducativo em Goiás: uma discussão sobre violência juvenil e políticas públicas - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research has as its object the socio-educational system, delimited in the system of Goiás. The justification for the choice of this object and delimitation is due to the tragedy that resulted in the death of ten young people who were under the responsibility of the Provisional Internment Center (CIP) in Goiânia - GO, a movement that left the researcher restless and gave rise to several questions. One of these questions underpins this research, configuring itself by "What is the harmony of the socio-educational system in Goiás with Law No. 8.069/1990 - Statute of Children and Adolescents (ECA) and Law No. in the State of Goiás (SINASE)?” Thus, the general objective is to analyze the socio-educational system in Goiás and its harmony with Law No. SINASE). To this end, the specific objectives are configured by discussing institutions, youth and youth violence, presenting public policies for childhood and youth, presenting ECA and SINASE and analyzing the pedagogical proposal of the socio- educational system of Goiás. The research is characterized as qualitative, bibliographical in nature, approaching the dialectical historical materialism, starting from the general to the particular and looking for contradictions. For the constitution of the methodology, contributions from authors such as Viana (2003), Faleiros (1995), Faleiros (2004), Rizzini (1995, 2017), Marx and Engels (2007) as well as the documents ECA, SINASE, LDB, PPP and Internal Rules of Colégio Estadual Vida Nova. The research pointed out that the socio-educational system in Goiás is in line with the ECA and SINASE, by the institutions that offer this service, as well as by documents such as the PPP, Internal Regulations and State Decrees that organize the service offered. But, this symptom appears distant because it is an unhealthy environment, because it was not planned for that. The dissertation is structured by chapters that initially address institutions, youth, violence, then public policies for childhood and youth and finally the socio-educational system in Goiás, youth violence and pedagogical proposals.
Socio-educational system in Goiás: a discussion about youth violence and public policies
Keywords: Sistema socioeducativo - Proposta Pedagógica; Sistema socioeducativo - Segregação; Sistema socioeducativo - Violência; Sistema socioeducativo - Lei no 8.069/1990 - Lei no 12.594/2012; Socio-educational system - Pedagogical Proposal; Socio-educational system - Segregation; Socio-educational system - Violence; Socio-educational system - Adolescent; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::EDUCACAO